Current status and trends in the study of intestinal flora in cognitive disorders: a bibliometric and visual analysis - Zhang, Qi; Gao, Zhenmei; Deng, Yunqing; Xu, Xiangqing; Sun, Wenyu; Liu, Rui; Zhang, Tianao; Sun, Xilei (Frontiers in Microbiology, 2025)
BackgroundCognitive impairment is a decline in people’s ability to think, learn, and remember, which has some impact on an individual’s daily activities or social functioning. Microbial toxins and metabolites from dysregulated gut microbiota directly interact with the intestinal epithelium. This interaction triggers neuroinflammation and neurodegeneration in the central nervous system, ultimately impairing cognitive function. It has been found that modulation of gut flora can be an effective intervention to improve cognitive dysfunction. This study is the first to summarize and outline the global research status and trends in this field from a bibliometric perspective, providing reference and guidance for future research in this field.MethodsBased on the Web of Science Core Collection (WoSCC) database, Literature on gut flora and cognitive impairment published between 1999–2025 was searched. Bibliometric analysis was performed using VOSviewer and CiteSpace software to analyze the data on countries, institutions, authors, journals, keywords, citations, and to generate visual maps.ResultsA total of 1,702 pieces of related literature were retrieved. The overall trend of publication is increasing. China has published the largest number of papers, and Huazhong University of Science & Technology and Kim, Dong-Hyun were the institutions and individuals with more publications. The most frequently cited journal is SCI REP-UK. The most frequent keywords are gut microbiota, followed by Alzheimer’s disease, cognitive impairment, Brain, oxidative stress and Inflammation.ConclusionIn recent years, the research application of gut flora in the treatment of cognitive impairment has made remarkable progress. Oxidative stress and inflammatory response have become the main research hotspots for gut flora to improve cognitive impairment in patients. The gut-brain axis plays an important role in the study of the mechanism of action. Short-chain fatty acids are the focus of research on gut microbial metabolism. Fecal microbial transplantation technology is increasingly being used as an emerging method for the application of intestinal flora. Modifying the gut flora by modifying diet and exercise may be an effective strategy to prevent and improve cognitive dysfunction in the future. Future studies may focus more on gender differences in the role of gut flora in the modulation of cognitive function.